2021
DOI: 10.3390/molecules26020427
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Antiviral Therapy for Subacute Sclerosing Panencephalitis

Abstract: Subacute sclerosing panencephalitis (SSPE) is a late-onset, intractable, and fatal viral disease caused by persistent infection of the central nervous system by a mutant strain of the measles virus. Ribavirin intracerebroventricular therapy has already been administered to several SSPE patients in Japan based on fundamental and clinical research findings from our group, with positive therapeutic effects reported in some patients. However, the efficacy of this treatment approach has not been unequivocally estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 94 publications
0
17
0
3
Order By: Relevance
“…3 Isoprinosine is also known to prolong survival of patients suffering from SSPE, the 8-year survival rate wars 61% in patients who were given Isoprinosine as compared to only 8% in patients who were not administered Isoprinosine. 21 Within a trial not comprising of a concurrent placebo control group, 35% of subjects who were administered Isoprinosine were stabilized or their condition was substantially better at a much higher rate than a rate of only 5% to 10%. 27 Several studies that evaluated the use of Isoprinosine in curing SSPE and their results are mentioned in Table 2.…”
Section: Anti-viralsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Isoprinosine is also known to prolong survival of patients suffering from SSPE, the 8-year survival rate wars 61% in patients who were given Isoprinosine as compared to only 8% in patients who were not administered Isoprinosine. 21 Within a trial not comprising of a concurrent placebo control group, 35% of subjects who were administered Isoprinosine were stabilized or their condition was substantially better at a much higher rate than a rate of only 5% to 10%. 27 Several studies that evaluated the use of Isoprinosine in curing SSPE and their results are mentioned in Table 2.…”
Section: Anti-viralsmentioning
confidence: 99%
“… 28 However, a study has shown that the oral administration of Ribavirin does not affect SSPE patients, mainly because the concentration required to deliver a therapeutic effect were not reached within the CSF. 21 In a limited number of random trials a little beneficial effect is shown when used together with Thymic Humoral Factor, Amantadine, steroids, and plasmapheresis intraventricular IFN and anti-CD 20 antibodies. 24 CSF measles antibody titers in SSPE patients are lowered by Ribavirin, decreasing neurological symptoms without any adverse effects.…”
Section: Anti-viralsmentioning
confidence: 99%
See 3 more Smart Citations